The production of methyl esters from waste frying oil by microwave method - Rahmanlar, Isa; Yucel, Sevil; Ozcimen, Didem (WILEY, 2012)
Alcoholysis of waste frying oil (WFO) was studied by using microwave irradiation to examine alcoholization reaction factors which affect the purity of the ester product, including the molar ratio of methanol to WFO, the amount of alkaline catalyst and the reaction time. The alcoholysis reactions were carried out by using WFO, methanol and sodium hydroxide as the catalysts at 64 degrees C. In order to characterize the reaction conditions for methyl ester production, a series of experiments were carried out with methanol/WFO molar ratios between 6 and 18, and catalyst/WFO weight ratios between 0.5 and 1.5%. The results showed that the most important parameter affecting the reaction is the amount of sodium hydroxide. The best catalyst amount was found as NaOH 1% from the WFO. A higher methyl ester purity was obtained in 13 min. In the presence of 1% of NaOH molar ratios varying from 6:1 to 18:1 in 3 min of reaction time, the purity of methyl ester was 93.8397.20%. However, difficulties were observed in separation process above 9:1. The experimental results indicated that microwave-assisted alcoholysis efficiently produced pure methyl esters in methyl ester quality in a short reaction time. (c) 2011 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: alcoholysis; methyl esters; microwave; waste frying oil; IN-SITU ESTERIFICATION; COOKING OIL; BIODIESEL PRODUCTION; TRANSESTERIFICATION; CATALYST; Engineering